Effectiveness of preventive interventions on adolescents’ depression and suicidal tendency: a systematic review of randomized controlled trials - Ghazal, Lubna; Cui, Naixue; Fenglin, Cao; Froelicher, Erika Sivarajan; Shimbrer, Mulugeta Shegaze (Frontiers in Psychology, 2025)
IntroductionThis study was conducted to review the effectiveness of preventive mental health interventions for adolescents (aged 11–19 years) in reducing depression and suicidal tendencies.MethodsA systematic search was conducted to identify randomized controlled trials (RCTs) from the databases PubMed, CINAHL, EMBASE, and APA PsycINFO for the period 2011–2024. Studies were included based on strict inclusion/exclusion criteria, selecting those that reported preventive interventions addressing depression and suicidal tendencies among adolescents. The systematic review registration number is CRD42023384321.ResultsOut of 1,210 studies, 13 RCTs were incorporated. The interventions yielded varied outcomes, with approximately half of the RCTs demonstrating reductions in depression and suicidal tendencies, comparable to the control group. Post-intervention, the majority of interventions exhibited mild to moderate effect sizes; however, further research is warranted to assess their long-term efficacy. Cognitive-behavioral therapy (CBT)-based psychoeducation interventions served as the primary approach, often implemented in school settings. However, these interventions were primarily delivered by specialists rather than teachers. Parental involvement in treatment emerged as a potential factor that could enhance the effectiveness of preventive interventions.Discussion and conclusionWhile numerous interventions in this review showed effects comparable to control groups, the diversity in methodology, intervention types, and outcome measures poses challenges in drawing definitive conclusions. Therefore, future research should prioritize addressing these methodological discrepancies within their respective contexts.